2008
DOI: 10.1093/beheco/arn050
|View full text |Cite
|
Sign up to set email alerts
|

Optimal individual positions within animal groups

Abstract: 1Animal groups are highly variable in their spatial structure, and individual fitness is 2 strongly associated with the spatial position of an animal within a group. Predation 3 risk and food gains are often higher at the group peripheries; thus, animals must trade 4 off predation costs and foraging benefits when choosing a position. Assuming this is 5 the case, we firstly use simulation models to demonstrate how predation risk and food 6 gains differ for different positions within a group. Secondly, we use th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
66
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 54 publications
(35 reference statements)
0
66
0
Order By: Relevance
“…When resting, the spatial geometry of the herd could also be determined by the costs and benefits of an individual's spatial position within the group (Hirsch 2007). Previous studies have, in general, reported that peripheral individuals experience greater predation risk, whereas those in the centre of the group have access to fewer food resources (e.g., Hamilton 1971;Parrish and Edelstein-Keshet 1999;Focardi and Pecchioli 2005;Morrell and Romey 2008). However, since predation on the forest buffaloes in our study was never observed, antipredator behaviour seems not a good reason that influences herd size and aggregation in open habitat in this specific case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When resting, the spatial geometry of the herd could also be determined by the costs and benefits of an individual's spatial position within the group (Hirsch 2007). Previous studies have, in general, reported that peripheral individuals experience greater predation risk, whereas those in the centre of the group have access to fewer food resources (e.g., Hamilton 1971;Parrish and Edelstein-Keshet 1999;Focardi and Pecchioli 2005;Morrell and Romey 2008). However, since predation on the forest buffaloes in our study was never observed, antipredator behaviour seems not a good reason that influences herd size and aggregation in open habitat in this specific case.…”
Section: Discussionmentioning
confidence: 99%
“…Magurran 1993;Parrish and Hamner 1997;Ruckstuhl 1998;Krause and Ruxton 2002;Ruckstuhl and Kokko 2002;Turner et al 2005;Hay et al 2008;Korte 2008b;Morrell and Romey 2008). These factors include feeding and foraging efficiency, energy expenditure, the time spent on vigilance behaviour, predation risk, group size, sexual segregation and reproductive opportunities.…”
Section: Introductionmentioning
confidence: 99%
“…While schooling can provide significant advantages to individual fish in terms of both predator avoidance [2] and foraging success [3], the exact benefits gained by school members depend on spatial location within the school [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…; Hirsch & Morrell ), access to food (Robinson ; Barta et al. ; Di Bitetti & Janson ; Morrell & Romey ) and patterns of social interaction with other group members (Baldwin & Baldwin ). The major theory used to predict the influence of within‐group spatial position on predation risk is the ‘selfish herd’ effect (Hamilton ).…”
Section: Introductionmentioning
confidence: 99%